2004
DOI: 10.4049/jimmunol.172.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-Reactive Class I-Restricted Cytotoxic T Cell Clones Are Stimulated by Dendritic Cells Loaded with Synthetic Peptides, but Fail to Respond to Dendritic Cells Pulsed with Melanoma-Derived Heat Shock Proteins In Vitro

Abstract: Immunization with heat shock proteins (hsp) isolated from cancer cells has been shown to induce a protective antitumor response. The mechanism of hsp-dependent cellular immunity has been attributed to a variety of immunological activities mediated by hsp. Hsp have been shown to bind antigenic peptides, trim the bound peptides by intrinsic enzymatic activity, improve endocytosis of the chaperoned peptides by APCs, and enhance the ability of APCs to stimulate peptide-specific T cells. We have investigated the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…Immunotherapies using HSPs to generate specific antitumor responses have been evaluated in clinical studies (16, 39 -41). In this report the gp96 -7/9-mer peptide complex and its terminal fragment-7/9-mer peptide complex could not elicit obvious peptide-specific CTL in mice, consistent with recent observations in vitro (42). However, when mixed with different amounts of peptides directly, gp96 and its N-terminal fragment (N333) showed adjuvant effects in enhancing the peptide-specific CTL response, and this response was peptide concentration dependent.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Immunotherapies using HSPs to generate specific antitumor responses have been evaluated in clinical studies (16, 39 -41). In this report the gp96 -7/9-mer peptide complex and its terminal fragment-7/9-mer peptide complex could not elicit obvious peptide-specific CTL in mice, consistent with recent observations in vitro (42). However, when mixed with different amounts of peptides directly, gp96 and its N-terminal fragment (N333) showed adjuvant effects in enhancing the peptide-specific CTL response, and this response was peptide concentration dependent.…”
Section: Discussionsupporting
confidence: 76%
“…The findings implied that the N-terminal part of gp96 might contain the very motif to stimulate the innate immune system. However, additional work is necessary to completely rule out the possibility that proteins copurified with gp96 may contribute to its immunological effect, as suggested by several recent publications (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…These workers, too, conclude that stress protein-peptide complexes are unlikely to contribute to the phenomenon of cross-priming, rather, larger (poly)peptide proteasome substrates serve as the physiological message (Norbury et al 2004). Consistent with this view, Fleischer et al (2004) reported that though complexes of gp96 and synthetic melanoma peptide antigens can be efficiently processed by APC to yield stimulation of melanoma reactive CTL clones, no significant melanoma reactive CTL activity was obtained from APC pulsed with melanoma-derived gp96.…”
Section: A Brief History Of the Life Of A Peptidesupporting
confidence: 57%
“…J76 cells are TCRa and TCRb deficient but express all CD3 components. The human CMV-specific T cell clone T21 (Vb20) (submitted for publication) and the Melan-A-specific T cell clone InRi1 (Vb14) [28] were cultured with RPMI 1640 medium supplemented with 10% human serum (Valley Biomedical, Winchester, USA), 100 U/mL penicillin/streptomycin, 2 mM glutamine, 10 ng/ mL anti-CD3 mAb (Janssen-CILAG, Neuss, Germany), 50 U/mL IL-2, and 2 ng/mL IL-15. As feeder cells, 2.5 Â 10 7 allogeneic PBMC (irradiated with 30 Gy) and 5 Â 10 6 B lymphoblastoid cell lines (irradiated with 100 Gy) from healthy donors were added per T30 tissue culture flask (Greiner).…”
Section: Cells and Peptidesmentioning
confidence: 99%
“…Cytolytic activity was analyzed in a standard 4-h chromiumrelease assay as described [28]. T2 cells were labeled with 100 lCi 51 Cr (ICN Biochemicals, Irvine, USA) and then loaded with 10 lg/mL peptide.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%